STUDENT'S SPEAKING SKILL IN ENGLISH MATHEMATICS COURSES WITH THE SILENT WAY METHOD - Rohmah Indahwati (Universitas Madura, 2022)
The purpose of this study was to determine student responses to English Mathematics lectures using the silent way method and also to determine students' speaking skills when the method was applied. Aspects assessed from speaking skill include grammar, vocabulary, comprehension, fluency, and pronunciation. This study uses quantitative and qualitative descriptive methods which aim to see the responses and learning outcomes of students in the form of speaking skills using English mathematics with Integer and Fractions material. Based on the results of the research that has been carried out, it can be concluded that the responses and speaking skills of students in English mathematics lectures on the topic of integers and fractions at Madura University are generally good. The response given by students to lectures with this method is positive. Meanwhile, the speaking ability score which includes 5 aspects is also good, namely the students' grammar mastery of 35.9% who got a score of 3 in the very good category, vocabulary mastery of 47.2% in the very good category, and 41.5% of the comprehension mastery with very good category, fluency mastery of 20.7% in very good category, mastery of pronunciation indicator by 16.2% in very good category.